EARLY PROTEROZOIC AGE OF THE TYRKANDIN FAULT ZONE, THE ALDAN SHIELD: U-PB DATING OF FRAGMENTS OF SINGLE ZIRCON GRAINS - Sal'nikova E.B.; Kotov A.B.; Pertsev N.N.; Yakovleva S.Z.; Glebovitsky V.A.; Fedoseenko A.M.; Kazansky V.I.; Plotkina Yu.V. (My University, 2006)
This paper is devoted to geochronological study of the Tyrkandin fault zone, which is one of the largest sutures in the eastern Aldan Shield. This 20-km-wide zone extends more than 500 km. It is characterized by positive magnetic linear anomalies. In addition, the zone coincides with a large gravity step, which separates blocks with different structures of the earth’s crust. It should also be noted that the Tyrkandin fault zone hosts numerous mafic and ultramafic bodies. In addition, unlike surrounding granulites, K- and K–Na-granitoids, which are widespread in this zone, form migmatite leucosome, pegmatoid granite veins, and concordant granite gneiss and gneissic granite bodies.
Keywords: Tyrkandin fault zone; Aldan shield; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой